Trends in the global burden of aortic valve calcification disease in the working-age population from 1992 to 2021 - Wu, Songzhe; Yang, Weiguang; Li, Yixin; Wei, Tao; Sun, Yaodong; Xia, Lin; Zhu, Yan; Wu, Naishi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCalcific aortic valve disease (CAVD) is a degenerative condition marked by aortic valve thickening and calcification, leading to stenosis or regurgitation, with rising prevalence in developed countries.ObjectivesThis study aimed to analyze the epidemiological trends and disease burden of CAVD in the global working-age population (defined in this study as the age group of 15 to 64 years) from 1992 to 2021. It further examined differences by Sociodemographic Index (SDI) regions and gender, providing insights for public health strategies.MethodsData were obtained from the Global Burden of Disease (GBD) 2021 study, using age-standardized rates (ASR) to adjust for differences in age distribution across populations, allowing for more accurate comparisons of disease burden over time and between regions. Trends were analyzed using Joinpoint regression, and health disparities were assessed using Slope and Concentration Indexes. The impact of demographic factors on CAVD burden was explored through decomposition analysis.ResultsFrom 1992 to 2021, CAVD prevalence in working-age populations rose from 1.30 to 2.65 million cases (103.43% increase). The results of multiple analysis models (including age-period-cohort model, decomposition analysis and frontier analysis) of the working-age population showed that the prevalence of CAVD peaked at the age of 64, and the prevalence of CAVD was significantly higher in males than in females. Population growth and ageing are the main drivers of the increasing burden of disease, with the highest burden in high SDI regions, especially Europe. These findings highlight the need to implement targeted interventions in high-risk populations.ConclusionsThe burden of CAVD in working-age populations is rising. Despite age-standardized death rate (ASDR) and age-standardized disability-adjusted life years (ASDALY) declines, the overall increase in cases requires targeted prevention and management strategies, especially in high-burden settings. Effective interventions are critical for reducing the global CAVD burden.